2013
DOI: 10.2174/1874401x01306010013
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Assessment Technique to Assist Management of the White Shark (Carcharodon Carcharias) Cage Dive Industry, South Australia

Abstract: Port Lincoln, South Australia is the departure port for the only white shark, Carcharodon carcharias, cage dive industry in Australia. Established in the early 1960's as a niche tourism venture, the industry has recently undergone a rapid expansion to accommodate greater passenger numbers, more tourism operators, and additional infrastructure aimed at capturing a greater proportion of the tourist dollar. However, to date, there has been no assessment of growth in the industry. We have used the operator logbook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…carcharias to approach the platform used for observation either making them more likely or less likely to be observed. Shark‐cage diving, involving chumming, has been a feature of the Neptunes Islands environment for over three decades (Bradford & Robbins, ). Cage‐diving operations have been shown to influence local residency times and distribution of C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carcharias to approach the platform used for observation either making them more likely or less likely to be observed. Shark‐cage diving, involving chumming, has been a feature of the Neptunes Islands environment for over three decades (Bradford & Robbins, ). Cage‐diving operations have been shown to influence local residency times and distribution of C .…”
Section: Discussionmentioning
confidence: 99%
“…The Neptune Islands hold some of the largest aggregations of pinnipeds in Australian waters (Shaughnessy & McKeown, ) and have been the site of an active cage‐dive industry for C . carcharias since the 1970s (Bradford & Robbins, ). Acoustic and satellite‐based telemetry tagging at the Neptune Islands have identified that C .…”
Section: Introductionmentioning
confidence: 99%
“…The income from these activities contributes millions of dollars annually to local and regional economies (Topelko and Dearden, 2005;Vianna et al, 2012). For example, at Port Lincoln (South Australia), the only white shark cage diving industry in Australia, the industry grew from an average 67 days per year prior to 1997 to 287 in 2011 when it was estimated that approximately 5200 passengers spent USD 5.28 annually to view the white shark (Bradford and Robbins, 2013).…”
Section: Extent Of Non-consumptive Wildlife-oriented Tourismmentioning
confidence: 99%